Analysis of Determinants of Inflation Dynamics in Several ASEAN Countries - Alifah Humairah; Dwita Sakuntala; Wahyu Indah Sari (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the determinants of inflation dynamics in several ASEAN countries, namely Indonesia, Malaysia, Thailand, and Brunei Darussalam during the period 2005-2024. The independent variables used include Gross Domestic Product (GDP), lending interest rates, money supply, and West Texas Intermediate (WTI) world oil prices. This study uses a quantitative approach with panel data regression methods. The results of the model testing indicate that the Common Effect Model (CEM) is the most appropriate model following the Chow test and the LM test. Partially, the results show that GDP, lending rates, and WTI world oil prices have a positive and significant effect on inflation. Simultaneously, all independent variables have a significant effect on inflation. This finding indicates that inflation dynamics in the ASEAN countries studied are influenced by a combination of domestic and global factors.